Rural Marketing of Select Fast Moving Consumer Goods in Punjab - Garga, Pawan; Ghuman, Kaminder; Dogra, Balram (Indian Journal of Marketing, 2009)
This research paper based on primary data examines the domain of Rural Marketing for the select FMCGs for the state of Punjab with an objective to develop an insight into the buying behaviour of rural consumers.Instead of smaller packages, medium packages were reported to be the most preferred with only exception of shampoo. The quality of goods stocked by the rural retailer was reported to be average and majority of respondents reported lack of trust in the matter of the advertisement with significant variations across the different districts. From testing of hypothesis relationship was observed to be existing: between consumer’s purchase decisions on the basis of price and the select FMCG product categories; consumer opinion about inferior quality of loose products and district of respondents; consumer’s opinion about the quality of products stocked by rural retailer and district to which they belong; rural consumer’s trust on the matter of the advertisements and the different districts. It is recommended that neither rural Punjab should be treated as single homogeneous market nor different FMCG products categories be planned in a similar manner. Specific marketing strategies based on the different elements of Marketing Mix have also been developed in the paper.